Peripheral pulmonary artery aneurysm presenting as a solitary pulmonary nodule - Tamagno, Mauro Federico Luis (Autops Case Rep, 2015)
We report the case of a 63-year-old female patient who was evaluated due to a solitary pulmonary nodule. The final diagnosis was a solitary peripheral pulmonary artery saccular aneurysm. The patient was submitted to a pulmonary lobectomy with excellent recovery. Peripheral pulmonary artery aneurysms that arise from segmental or intrapulmonary branches are extremely rare, and their management is still controversial.